Effects of chirality and inhomogeneous growth on the morphology of plant tendril. (1st November 2021) - Zhao, Hui-Chuan; Bian, Li-Chun; Zhang, Tao; Dong, Jia-Jun
Abstract: By controlling the growth rate, biomaterials with chiral microstructure can produce nonuniform prestress and then form chiral morphologies, such as twisted biological filaments, while it is not clear how the chiral microstructure of biomaterials affects the formation and movement of its macro chiral morphologies under the action of uneven prestresses. In this work, a double-layered composite beam model considering the chiral microstructure of biological materials based on experimental observations is established. The influences of inhomogeneous growth and chiral microstructure on the formation of the chiral morphologies of tendrils are considered as a typical example and discussed in detail. The results show that the macro chiral phases of plant tendrils provide a remarkable dependence on their chiral microstructures.